Graphene oxide film as a protective barrier for Mg alloy: Worse or better is dependent on a chemical reduction process. (April 2019) - Chu, J.H.; Tong, L.B.; Wen, M.; Jiang, Z.H.; Wang, K.S.; Zhang, H.J.
Abstract: Poor corrosion and wear resistances of Mg alloys have severely restricted their extensive applications. Here we report a comparative study of bioinspired graphene oxide(GO)/reduced graphene oxide (rGO)-polyvinyl alcohol (PVA) composite films with nacre-like architectures on Mg alloys, via a facile reduction process. GO-PVA film remarkably deteriorates the corrosion resistance of Mg alloy, with an increased corrosion rate of 3.657 × 10 −5 from 2.038 × 10 −5 A/cm 2, due to its loose microstructure and typical cathodic reaction. In contrast, the removal of oxygen-containing groups by chemical reduction leads to a recovery of conjugated structure and reduces the intrinsic capillaries, and the corrosion rate of rGO-PVA film is 18 times lower than that of GO-PVA film, through hindering the galvanic corrosion and weakening the cathodic reaction. Additionally, the wear rate of Mg alloys protected by GO/rGO-PVA films remarkably decreases by 98.6% and 98.2%, respectively. The chemical reduction effectively decreases the cluster-stacked structure on the surface of the GO-PVA film and restricts its exfoliation behavior, which promotes the puckering effect and results in a slightly enhanced wear behavior of the rGO-PVA film. The current study demonstrates a potential prospect of the bioinspired graphene-based film, which is beneficial to achieving the integrated anti-corrosive/wearable performances of metallic materials. Graphical abstract: Image 1